2010
DOI: 10.1016/j.ecolecon.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Balancing state and volunteer investment in biodiversity monitoring for the implementation of CBD indicators: A French example

Abstract: International audienceAccording to the Convention on Biological Diversity (CBD), states have to provide indicators in order to assess the performance of their initiatives for halting the loss of biodiversity. Sixteen headline indicators have been identified for monitoring the CBD targets. Of these indicators only one, "Trends in the abundance and distribution of selected species," is a direct headline indicator of "non-exploited" biodiversity. In France, the implementation of this indicator is completely depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 38 publications
0
52
1
5
Order By: Relevance
“…En France, 72 % des suivis de biodiversité sont réalisés par des bénévoles (Levrel et al, 2010). Comme dans la majorité des sciences de la nature, qualifiée de « science de plein air » (Callon et al, 2001), où la récolte de données sur de vastes espaces géographiques et de longues périodes de temps est particulièrement importante, la participation citoyenne à la recherche en biodiversité est une source de travail et de compétences non négligeables (Baretto et al, 2003;Bonney et Labranche, 2004;McCaffrey, 2005;Charvolin et al, 2007;Heaton et al, 2011), notamment en botanique, particulièrement sujette à la participation des amateurs (Keeney, 1992;Secord,1994;Livesey, 2005).…”
Section: Resultsunclassified
“…En France, 72 % des suivis de biodiversité sont réalisés par des bénévoles (Levrel et al, 2010). Comme dans la majorité des sciences de la nature, qualifiée de « science de plein air » (Callon et al, 2001), où la récolte de données sur de vastes espaces géographiques et de longues périodes de temps est particulièrement importante, la participation citoyenne à la recherche en biodiversité est une source de travail et de compétences non négligeables (Baretto et al, 2003;Bonney et Labranche, 2004;McCaffrey, 2005;Charvolin et al, 2007;Heaton et al, 2011), notamment en botanique, particulièrement sujette à la participation des amateurs (Keeney, 1992;Secord,1994;Livesey, 2005).…”
Section: Resultsunclassified
“…In the EU, wild birds are protected by The Birds Directive 12 and in a number of European countries they are monitored by networks of volunteers through the Pan-European Common Bird Monitoring Scheme, jointly led by BirdLife International and the European Bird Census Council (EEA, 2013). In France, the National Museum of Natural History organises the Vigie-Nature monitoring programme, which relies on citizen scientists and saves the French government an estimated €1-4 million per year (Levrel et al, 2010). A 2011 study based on volunteer-collected data from the Swedish Bird Survey concluded that monitoring by citizen scientists could prove useful in future assessments of wild bird populations and help to inform more targeted and efficient conservation efforts (Snäll et al, 2011).…”
Section: Development In Environmental Research Monitoring and Policymentioning
confidence: 99%
“…There has been a recent proliferation of studies in the marine environment, with a 2014 review identifying 227 publications with a reference to citizen science (Thiel et al, 2014). The value of citizen science to support monitoring is significant (Levrel et al, 2010;Defra, 2011;Theobald et al, 2015) and governments are recognizing the potential benefits of using citizen science (Postnote, 2014).…”
Section: Citizen Sciencementioning
confidence: 99%